Rapid Detection of Copper in Biological Systems Using Click Chemistry. Issue 14 (1st March 2018) - Zheng, Wenshu; Li, Huiling; Chen, Wenwen; Zhang, Jiangjiang; Wang, Nuoxin; Guo, Xuefeng; Jiang, Xingyu
Abstract: A fast (1 min), straightforward but efficient, click chemistry‐based system that enables the rapid detection of free copper (Cu) ions in either biological fluids or living cells without tedious pretreatment is provided. Cu can quickly induce the conjugation between graphene oxide (GO) and a fluorescent dye via click reaction. On the basis of the high specificity of bioorthogonal reaction and the effective quenching ability of GO, the assay studied in this paper can respond to Cu ions in less than 1 min with excellent selectivity and sensitivity, which is the fastest sensor for Cu as far as it is known. In addition, the application of this system is verified by performing assays in living cells and untreated urine samples from patients suffering from Wilson's Disease. Such a Cu detection system shows great promises in both fundamental research and routine clinical diagnostics. Abstract : A straightforward but efficient, graphene oxide based system enables the rapid detection of free Cu ions in either biological fluidics or living cells without tedious pretreatment. The assay shows great promise in both fundamental research and routine clinical diagnostics.